TOWARD ORGANIZATIONAL EVIDENCE-BASED MANAGEMENT IN HEALTHCARE ORGANIZATIONS - Hatem H. Alsaqqa (Rojan GÜMÜŞ, 2020)
Purpose - To date, relatively little evidence has been published as to what represents an effective evidence-based management in healthcare organizations. Existing studies are rarely conceived or developed with respect to organizational factors determining whether such studies succeed or fail. One of the challenges in linking organizational factors to evidence-based management is to identify the focus at which characteristics of healthcare organizations and management of knowledge resources are most obvious. This paper sets out to sense this issue. Design/methodology/approach - The paper suggests a conceptual framework through reviewing the existing literature on organizational factors and evidence-based management in the healthcare sector. A new conceptual approach as to how organizational factors and managerial-decision process can be more effectively linked through the organizational-level of healthcare organizations. Findings - Recommendations are provided with regard to how future healthcare organizations can approach the evidence-based management from a logically wide organizational-level and context perspective. Originality/value - The present paper represents an attempt to link organizational factors and evidence-based management in a more meaningful way. A conceptual model has been provided as a way to frame and imagine the organizational circle of producing management evidence. Keywords - Context; Organizational characteristics; Organizational culture, Evidence-based management, Healthcare organizations